2013
DOI: 10.1128/jvi.02860-12
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sensing-Independent Inhibition of Herpes Simplex Virus 1 Replication by DAI/ZBP1

Abstract: DNA-dependent activator of interferon regulatory factor (DAI) acts as a cytosolic B-form DNA sensor that induces type I interferons. However, DAI is not required for DNA sensing in certain cell types due to redundancy of the DNA sensing system. Here, we investigated the effect of DAI on herpes simplex virus 1 (HSV-1) infection in HepG2 hepatocellular carcinoma cells. DAI transcription was induced after gamma interferon (IFN-␥) treatment or HSV-1 infection. HSV-1 replication was enhanced by DAI knockdown, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 47 publications
(66 reference statements)
1
49
0
Order By: Relevance
“…In contrast, DAI is dispensable for the DNA-triggered IFN production in mouse embryo fibroblasts and dendritic cells (44). Recent studies showed that DAI initiates necroposis of 3T3 cells in response to mouse CMV infection (47), and it inhibits HSV-1 replication by suppressing the expression of the viral ICP0 protein in hepatocellular carcinoma cells (48). These observations suggest that DAI can be involved in the antiviral responses through different mechanisms dependent on cell and virus types.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, DAI is dispensable for the DNA-triggered IFN production in mouse embryo fibroblasts and dendritic cells (44). Recent studies showed that DAI initiates necroposis of 3T3 cells in response to mouse CMV infection (47), and it inhibits HSV-1 replication by suppressing the expression of the viral ICP0 protein in hepatocellular carcinoma cells (48). These observations suggest that DAI can be involved in the antiviral responses through different mechanisms dependent on cell and virus types.…”
Section: Discussionmentioning
confidence: 89%
“…The different topology of HSV-1 DNA may release structural constraints on IFI16, making it accessible to bind ASC. Additional extensive studies beyond the scope of the present study are required to further examine the interactions of IFI16 with host and viral DNA and to determine if there is a direct interaction of IFI16 with the HSV-1 genome or if the interaction occurs through other proteins known to interact with IFI16 and HSV-1 DNA, such as p53 (21), BRCA1 (73), or proteins in ND10 domains (74).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the prevalent paradigm has been that the IFN production occurs in response to activation of the cytosolic sensors, whereas the TLRs located at the plasma membrane elicit a predominantly inflammatory response (4)(5)(6). In particular, until recently, TLR2 was known to sense bacteria and was thought not to be involved in recognition of viruses.…”
mentioning
confidence: 99%